Resolução de problemas de probabilidade no ensino médio: uma análise de erros em provas da OBMEP no Maranhão - FERREIRA, Thyago Araujo (2017)
Recognize the problems and central errors completed by High school students in explaining Probability problems is the paper’s main aim. It analyzed errors in OBMEP’s second step - Level 3 between 2015 and 2016 years in Maranh~ao. Therefore, it was elaborated by seven chapters, talking about: a short history and teaching about robability’s studies; The establishing measures of error classification will be analyze in resolution of OBMEP’s mistakes probability tests - Level 3 in 2015 and 2016 years of Maranh~ao and in the most frequent errors types analyzes about probability inquiries. In Cury’s (2008, 2009 and 2010) studies assurances the errors analysis on the students written records, established on the questions analysis of OBMEP’s probability content tests (Public Schools’ Brazilian Mathematics Olympiad) 2015 and 2016 years, from the floating reading steps of all material, union and categorization answers and management results.